Ölüme bağlı tasarruf yoluyla vakıf kurulması - Üçerler, Esra Ceren (My University, 2009)
I.ÖZET: Vakıflar Medeni Kanunu’n 102. maddesine göre, resmi senet veya ölüme bağlı tasarruf ile kurulur. Benim tez çalışma konum ölüme bağlı tasarruf yolu ile vakıf kurmadır. Türk Hukukunda şekli anlamda 2 türlü ölüme bağlı tasarruf mevcuttur. Bunlardan biri vasiyetname diğeri ise miras sözleşmesidir. Vasiyetnamenin tek taraflı bir hukuki işlem olmasına karşılık, miras sözleşmesi iki taraflı bir hukuki muameledir. Bu yüzden miras sözleşmesi ile vakıf kurma konusu tartışmalıdır. Ölüme bağlı tasarruflar numerus clauses ilkesine tabidirler. Bu yüzden yalnızca kanunda belirtilen şekli şartlara uyularak yapılabilirler. Ölüme bağlı tasarruf yoluyla kurulan bir vakıftan ancak tescilden önce caymak mümkündür. Vakfın en temel unsuru amaçtır. Vakfın amacı, belirli ve sürekli olmalıdır. Aynı zamanda amaç, imkansız ve yasak olmamalıdır. Vakıf tescil ile tüzel kişilik kazanır. Tüzel kişiliğin kazanılması ile mallar vakfa geçer. Şayet mirasbırakan vakfı kuraraken saklı pay sahibi mirasçıların paylarını veya alacaklıların haklarını ihlal etmiş ise, saklı pay sahibi mirasçılar ve alacaklılar bu haklarını tenkis davası ve tenkis defi veya iptal davası veya iptal defi ile ileri sürebilirler. Vakfın amacı imkansız hale gelmiş ise, vakıf aciz haline düşmüş ise vs. sebeplerle vakıf kendiliğinden sona erebilir. Vakfın yasak amaç güttüğü tespit edilirse Cumhuriyet Savcısının veya denetim makamının başvurusu ile mahkeme kararı ile vakıf sona erdirilebilir. Vakfın vakıf senedindeki sebeplerle de sona ermesi mümkündür. Vakfın sona ermesi ile tasfiye ve tahsis aşaması başlar. Sona eren vakıf Asliye Hukuk Mahkemesinde ve merkezi sicilde tutulan sicillerden silinir. Resmi gazete de ilan edilir. II.

Foundation is established with authentic deed or disposition mortis causa according to the Turkish Civil Code’s 102. Article. The subject of my thesis is establishing foundation with disposition mortis causa. In Turkish law, two kinds of disposition mortis causa exist. One of them is testament and the other one is testamentary contract. Although testamentary is an unilateral legal transaction, testamentary contract is a bilateral contract. Therefore, establishing a foundation with testamentary contract is arguable. Disposition mortis causa depends on numerus clauses principle so it has to be arranged according to the formal condition indicated in the law. Giving up establishing a foundation can only be possible before the registration. The most fundamental element of foundation is objective. The objective of the foundation has to be specific and constant. It should not be impossible and illegal. Legal nature of foundation established with disposition mortis causa is a legal transaction which is complimentary and an act of commitment. Foundation gains legal personality with registration. Properties will pass through the foundation after the foundation gains legal personality. If deceased violate the inheritance rights of heirs and creditor, the heirs and the creditors have the right to make an objection to this situation by reduction action or plea and action for nullity or plea. Foundation may come to an end by itself when its objections become impossible or insolvency etc. If it is realized that foundation drives illegal objections, the foundation can be dissolved by a court as a result of a public prosecutor’s motion or motion of a control office. Finally, foundation may come to an end because of the reasons indicated by the deceased in the foundation deed. After the foundation comes to an end winding up and allocation process begins. The foundation that came to an end is deleted from the register held in court of first instance and held in principal register. This occasion is announced in the official gazette.
Keywords: Özel Hukuk; Vakıflar